Regulatory and Modifying Role of Natural Populations of Entomophages in Biocenoses of the Exclusion Zone of the Chernobyl Nuclear Power Plant - Drozda, Valentin; Bondarenko, Ilona; Zagayko, Olga (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The level of regulatory and modifying role was estimated on example of ecological and trophic interactions of population of aphids and their entomophages – Aphidiidae and Aphelinidae. Long-term researches (1986–2012 years) were conducted in biocenoses of the exclusion zone of the Chernobyl nuclear power plant. This is primarily, woody and shrub plants, including fruit crops. Seasonal monitoring of aphid populations was carried out by known methods in entomology and parasitology. Regular collections are provided for subsequent identification of aphid species. The level of infection of different stages by parasites was determined in laboratory conditions. The species composition and level of predation were established. The level of regulation of aphids from side of entomophages was determined. This process was evaluated on the basis of statistical materials and biocenotic role of zoophages. The life strategies of aphids and their entomophages were formulated. The researches were carried out by route surveys of habitats and ecosystems in spring, summer and autumn periods and regular observations and counts of entomological populations in nature, followed by laboratory and field experiments. As result of conducted researches were found 9 species of aphids on plants of Rosaceae family. We have established that most of them prone to r-selection with accent on tactics of reproduction and trophic connections. The character and specificity of settlement of aphids on plants were identified. Their trophic specialization with respect to different organs of plants was determined. The character of harmfulness of larvae and aphid adults was investigated in detail. We have established that significant quantity of entomophages with population of aphids ecologically and trophically are associated, mainly various predators: ladybird beetles (Coccinellidae), Syrphidae, gall midges (Cecidomyiidae) and Chrysopidae. The types of functional reaction in system «aphids-aphidophages» were investigated. Modifying role of aphidophages in dynamic of strength of population of aphids was shown. Authors of this article have established that Aphidiidae are manifesting elements of regulatory role sporadically, parasitizing on insignificant part of effective population of aphids.